2473. How Does Acquiring a Vaccine-Preventable Disease Impact Parental and Physician Responses to Vaccine Hesitancy?. (26th November 2018) - Allan, Kate; Fallon, Barbara; Maguire, Jonathon; Tran, Dat
Abstract: Background: Vaccine hesitancy poses an urgent threat to public health. This study aims to determine the frequency of children diagnosed with vaccine-preventable diseases (VPDs) accompanied by parental vaccine hesitancy, how physicians counsel parents of these children, and parents' intentions to vaccinate thereafter. Methods: A one-time survey was sent to pediatricians and pediatric subspecialists through the Canadian Paediatric Surveillance Program (CPSP). Results: In total, 925 pediatricians responded to the survey. 196 (21%) reported having seen a patient in the preceding 12 months who was diagnosed with a VPD whereby the patient or a sibling was not vaccinated or vaccination was delayed by parental choice. The most commonly diagnosed VPDs were pertussis (31%), varicella (27%), and pneumococcal disease (10%). The vast majority (94%) of pediatricians indicated that the VPDs were not acquired outside of Canada. The child's vaccination status against the VPD prior to contracting the VPD was reported as follows: 81% (156/192) had no immunization and 19% had delayed immunization. When asked about intervention strategies, 23% (41/181) of respondents reported that they had used a formal strategy or structured approach to discuss vaccination with the vaccine-hesitant parent(s) prior to the patient contracting a VPD. 57% (101/178) reported that a formal strategy was used after the patient contracted the VPD. Respondents indicated that their impression was that 35% (64/183) of vaccine-hesitant parents would not vaccinate in the future; 33% (60/183) of respondents were unsure. 79% (147/186) of respondents reported that they were aware of existing tools to manage vaccine hesitancy (e.g., Canadian Paediatric Society Practice Point Working with vaccine-hesitant parents). Of those who were aware of existing tools, 69% (100/145) had used the tools. Conclusion: Pediatricians frequently encounter children with VPDs whose parents are vaccine hesitant. A substantial number of Canadian pediatricians are either unaware of existing tools to address vaccine hesitancy or are not using them. It was the pediatricians' impression that a significant proportion of vaccine-hesitant parents would not vaccinate in the future despite their children having acquired a VPD. Disclosures: All authors: No reported disclosures.